Analysis of radionuclide migration with consideration of spatial and temporal change of migration parameters due to uplift and denudation. Issue 1744 (2015) - Shimada, Taro; Takeda, Seiji; Mukai, Masayuki; Munakata, Masahiro; Tanaka, Tadao
ABSTRACT: Integrated safety assessment methodology that analyzes radionuclide migration reflecting the spatial and temporal changes of disposal systems was developed for a geological disposal site with uplift and denudation, and then some case analyses for an assumed site were carried out. The combination of uniform uplift and denudation has the largest effect on the radionuclide migration because the ground water flow velocity increases with decreasing depth from the ground surface. In the case without denudation, tilted uplift has more effect than uniform uplift because flow velocity in tilted uplift increases with increasing hydraulic gradient. The long-term change of the geological structures including the uplift and denudation, the hydraulic conditions, and the recharge and outlet of the ground water around a candidate site should be carefully investigated to determine the appropriate the place, depth and layout of the repository.